Plasma levels of β2-microglobulin are associated with atherosclerosis in patients with systemic lupus erythematosus: a cross-sectional cohort study. (August 2018) - Leffers, H C B; Hermansen, M L; Sandholt, B; Fuchs, A; Sillesen, H; Køber, L; Kofoed, K F; Faurschou, M; Jacobsen, S
Objective: The objective of this paper is to examine the association between plasma levels of β2-microglobulin (β2MG), a protein previously associated with atherosclerosis, and the presence of carotid plaque (CP) or coronary artery calcium (CAC) in a cross-sectional cohort study of patients with systemic lupus erythematosus (SLE). Methods: Patients with SLE were enrolled between June 2013 and May 2014. The presence of CP and CAC was assessed with ultrasonography and computed tomography scan, respectively. The presence of CP or CAC in the SLE patients was analyzed with respect to plasma levels of β2MG and renal function expressed as the estimated glomerular filtration rate (eGFR). Results: The study cohort consisted of 147 patients, 89% women and 95% Caucasians. The median age was 46 (range: 21–75) years with a median disease duration of 14 years. CP and CAC was observed in 29 (20%) and 57 (39%) of patients, respectively. CP or CAC was seen in 62 (42%) patients and was associated with the highest quartile of plasma β2MG in patients with eGFR ≥ 90 ml/min/1.73 m 2 ; OR = 18 (95% CI: 1.7–181). β2MG adjusted for eGFR was also associated with presence of CP or CAC in the total cohort. The exclusion of 25 patients with a prior history of cardiovascular disease did not change the observed associations. Conclusion: In this study, we found significant associations between imaging markers of atherosclerosis and high plasma levels of plasma β2MG. These data suggest that β2MG is a candidate for further study as a biomarker for atherosclerosis in SLE.